Pathological changes in the lungs and lymphatic organs of 12 COVID-19 autopsy cases. Issue 12 (29th September 2020) - Liu, Qian; Shi, Yu; Cai, Jun; Duan, Yaqi; Wang, Rongshuai; Zhang, Hongyan; Ruan, Qiurong; Li, Jiansha; Zhao, Lei; Ping, Yifang; Chen, Rong; Ren, Liang; et al.
Abstract: Systematic autopsy and comprehensive pathological analyses of COVID-19 decedents should provide insights into the disease characteristics and facilitate the development of novel therapeutics. In this study, we report the autopsy findings from the lungs and lymphatic organs of 12 COVID-19 decedents—findings that evaluated histopathological changes, immune cell signature and inflammatory factor expression in the lungs, spleen and lymph nodes. Here we show that the major pulmonary alterations included diffuse alveolar damage, interstitial fibrosis and exudative inflammation featured with extensive serous and fibrin exudates, macrophage infiltration and abundant production of inflammatory factors (IL-6, IP-10, TNFα and IL-1β). The spleen and hilar lymph nodes contained lesions with tissue structure disruption and immune cell dysregulation, including lymphopenia and macrophage accumulation. These findings provide pathological evidence that links injuries of the lungs and lymphatic organs with the fatal systematic respiratory and immune malfunction in critically ill COVID-19 patients.